2019
DOI: 10.3390/nu11010149
|View full text |Cite
|
Sign up to set email alerts
|

Limited Effects of Low-to-Moderate Aerobic Exercise on the Gut Microbiota of Mice Subjected to a High-Fat Diet

Abstract: Several studies have indicated that diet and exercise may modulate the gut microbiota in obese subjects. Both interventions were shown to alter the microbiota orthogonally. However, this relationship has not been fully explored. This study analyzed the effects of low-to-moderate aerobic training on the fecal microbiota of mice subjected to a high-fat diet (HFD). Here, 40 male mice (C57Bl/6) were divided into two groups with standard diet (SD; 12.4% lipid) and HFD (60.3% lipid) for four months. These groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 55 publications
(75 reference statements)
1
29
1
Order By: Relevance
“…Since the cafeteria diet used here [20] tends to produce a more severe metabolic phenotype than purified high-fat diets [35][36][37][38], which to our knowledge have been used in all studies investigating the interrelationship between exercise and diet on microbiome composition, the diet-induced effects on microbiome composition here may be more resistant to the effects of exercise than previously reported. Additionally, a number of rodent studies report no differences in overall microbiome composition with exercise [17,19], and there is evidence that this effect may be moderated by age [39] which may have contributed to the inconsistent findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the cafeteria diet used here [20] tends to produce a more severe metabolic phenotype than purified high-fat diets [35][36][37][38], which to our knowledge have been used in all studies investigating the interrelationship between exercise and diet on microbiome composition, the diet-induced effects on microbiome composition here may be more resistant to the effects of exercise than previously reported. Additionally, a number of rodent studies report no differences in overall microbiome composition with exercise [17,19], and there is evidence that this effect may be moderated by age [39] which may have contributed to the inconsistent findings in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome compositional changes were observed in mice maintained on a healthy diet following 6 weeks of moderate treadmill exercise [16] and after 16 weeks in mice fed a high-fat diet [18]. In contrast, eight weeks of low-tomoderate exercise did not confer microbiome compositional changes in mice fed a high-fat diet [19]. Furthermore, most studies examining the effects of treadmill exercise on fecal microbiome in diet-induced obesity used a design where exercise was co-administered with high-fat diet, making it difficult to translate the findings to people, in terms of implementing exercise after a history of unhealthy eating and obesity.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, previous studies have indicated that exercise-induced metabolic effects have the capability to positively reshape the gut microbiota in various animal models as well as humans (Codella et al, 2018). However, changes to the structure of the gut microbiota vary depending on the exercise intensity, mode, and time (Ribeiro et al, 2019;Mohr et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies have focused on observing the changes in microbiota and metabolism after training (Allen et al, 2018;Ribeiro et al, 2019), while this study focused on the changes in microbiota and metabolism during the process of improving exercise performance through training. The results of this study can provide reference for improving exercise performance, and the relationship between the changes in microbiota and metabolism and exercise performance found in the training process can provide ideas for improving exercise performance with gut microbiota as the entry point in the future.…”
Section: Introductionmentioning
confidence: 99%
“… 118 Interestingly, low or moderate training had only minimal impact in modulating the gut microbiome in mice fed high-fat diet after 8 weeks of treadmill training. 119 The abundance of Proteus and Vagococcus were changed upon exercise. However, the body composition was changed by the exercise.…”
Section: How Exercise Shapes the Gut Microbiomementioning
confidence: 99%